Motoric Mechanisms for the Emergence of Non-local Phonological Patterns - Tilsen, Sam (Frontiers in Psychology, 2019)
Non-local phonological patterns can be difficult to analyze in the context of speech production models. Some patterns—e.g. vowel harmonies, nasal harmonies—can be readily analyzed to arise from temporal extension of articulatory gestures (i.e. spreading); such patterns can be viewed as articulatorily local. However, there are other patterns—e.g. nasal consonant harmony, laryngeal feature harmony—which cannot be analyzed as spreading; instead these patterns appear to enforce agreement between features of similar segments without affecting intervening segments. Indeed, there are numerous typological differences between spreading harmonies and agreement harmonies. This suggests that there is a mechanistic difference in the ways that spreading and agreement harmonies arise. This paper argues that in order to properly understand spreading and agreement patterns, the gestural framework of Articulatory Phonology must be enriched with respect to how targets of the vocal tract are controlled in planning and production. Specifically, it is proposed that production models should distinguish between excitatory and inhibitory articulatory gestures, and that gestures which are below a selection threshold can influence the state of the vocal tract, despite not being active. These ideas are motivated by several empirical phenomena, which include anticipatory posturing before production of a word form, and dissimilatory interactions in distractor-target response paradigms. Based on these ideas, a model is developed which provides two distinct mechanisms for the emergence of non-local phonological patterns.